LEGISLATIVE PROVISION OF ADULT EDUCATION IN THE REPUBLIC OF POLAND AND UKRAINE: A COMPARATIVE ASPECT (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2024)
Background. The analytical article is devoted to the problem of legislative regulation of adult education in the Republic of Poland and Ukraine. The purpose of the article is to highlight the peculiarities of the legislative provision of adult education in both countries. The key role currently played by adult education in solving modern challenges, overcoming social inequality, is characterized and the development of this educational direction as an integral component of lifelong education is highlighted. The progressive changes that have taken place recently in the field of legal regulation in Poland and Ukraine are outlined.Methods. The following methods were used in the research process: descriptive (description of the current legislation in the field of adult education in Poland and Ukraine), historical (identification of changes in the researched phenomenon that occurred over time), comparative (identification of common and distinctive features of legislative provision in both countries) and inductive (formulating generalizations based on specific observations). The scientific explorations of Polish and Ukrainian scientists in the field of andragogy and adult education are characterized.Results. Based on the results of the analysis of legislative and regulatory documents (laws, regulations, government resolutions), it was concluded that the adult education system in Poland is regulated by a set of laws, the main ones of which are the Law on the Education System and the Law on Promotion of Employment and Labor Market Institutions.Conclusions. The importance of normative and legal provision of adult education in Ukraine is substantiated, the importance of which is strengthened by the conditions caused by the military aggression of the Russian Federation. The current legislative acts regulating individual components of adult education in Ukraine have been analyzed. The content of the draft Law on Adult Education has been revealed. A comparative analysis of the current legislative provision of adult education in Poland and Ukraine was carried out, in particular, similar and distinctive features characteristic of both countries were identified. The progressive changes that have taken place recently in the field of regulatory regulation in both countries are outlined. It has been established that the development of adult education systems in Poland and Ukraine reflects the leading general European trends and at the same time has mental features unique to them. The results of understanding the content of the study can be useful for the development of relevant legislation in both countries.
Keywords: adult education; education system; Law on Adult Education; legislative provision; lifelong learning; Republic of Poland; Ukraine